An analysis of pro-environmental attributes towards adolescents in penang using extended theory of planned behaviour - Basri, Nur Khairiyah (2015)
The energy consumption in transportation sector was mostly created by the individual likeness to use private motor vehicle. High dependency on private motor vehicles has contributed not only to the traffic problem but also accounted to carbon emission. This study aims to investigate the psychological factors that influencing the adolescents’ intention to be more pro-environmental. This study found that the behavioural intention was significantly influenced by the adolescents’ awareness towards consequences, attitude towards environment and public transport, the sentiment of moral obligation to change, and the perceived possibilities or difficulty to practice environmental friendly travel behaviour.